Computational predictions turning the isomers of alanine to generate distinct morphs of free-flowing salt crystals. Issue 25 (13th June 2018) - Si, Mrinal Kanti; Pramanik, Sumit Kumar; Hingu, Vinayak; Ganguly, Bishwajit
Abstract : Computational predictions suggest that α-alanine should modify the salt crystals from cubic to octahedron, while β-alanine can give rhombic dodecahedron, experimental studies corroborate the quantum chemical results. Abstract : The morphology of salt crystals has been an active area of research for decades and remains largely empirical. This study reveals the computational modeling guides to arrive at the correct answer, even for complex problems, such as the morphology of salt crystals with additives. There is no report on the two different morphologies of rock-salt crystals with two isomers of a single additive. Alanine isomers (α- and β-) can induce octahedron and rhombic dodecahedron morphologies in salt crystals. The computational study demonstrated that α-alanine preferentially interacts with {111} and β-alanine with {110} planes to yield such morphologies. The change in morphology with alanine can greatly influence the problem of the free-flowing issue of salt crystals.